Pemahaman Kompetensi Lintas Budaya bagi UNTSO (United Nations Truce Supervision Organization) untuk Memecah Kebuntuan dalam Penyelesaian Konflik Palestina-Israel [UNTSO Competence in Cross-Cultural Understanding to Break the Deadlock in the Settlement of the Israeli-Palestinian Conflict] - Raden Mas Jerry Indrawan (Universitas Pelita Harapan, 2017)
UNTSO was the first peacekeeping mission created by the United Nations. They have been in the Middle East since June 1948 with the task of overseeing the implementation of the ceasefire between Israel and Arab countries, including seeking resolution of the conflict between Israel and Palestine. One of the reasons many UN peace missions fail, including UNTSO, was because the peacekeepers do not have the ability to understand the local culture in which they are placed. One of the main difficulties faced by peacekeepers in a conflict involving two groups with two different cultures is uncertainty about cultural values. UNTSO personnel very rarely received training as such and like the usual army, their tendency is to use violence to solve conflicts. There should be a special cultural training focused on developing an understanding of the cultural context, such as background orientation, origin, conflict parties, history, religion, customs, and local community language. This paper tries to provide an analysis through an understanding of cross-cultural competency, which is expected to provide recommendations for resolving the Palestinian-Israeli conflict.